Art, Play, Labour: the Music Profession in Germany (1850-1960) - Rempe, Martin (Brill, 2023)
Germany is considered a lauded land of music: outstanding composers, celebrated performers and famous orchestras exert great international appeal. Since the 19th century, the foundation of this reputation has been the broad mass of musicians who sat in orchestra pits, played in ensembles for dances or provided the musical background in silent movie theatres. Martin Rempe traces their lives and working worlds, including their struggle for economic improvement and societal recognition. His detailed portrait of the profession 'from below' sheds new light on German musical life in the modern era.